Embedding Research-Based Learning in Undergraduate Engineering Curriculum: A Case Study on Material Selection Pedagogy - M., Poornesh; DSouza, Smitha Maria (Journal of Engineering Education Transformations, 2026)
This study presents a structured model for integrating Research-Based Learning (RBL) into the second-year Material Selection module of an undergraduate mechanical engineering program. Recognizing the gap between theoretical knowledge and real-world application, the model embeds an interdisciplinary, research-oriented assignment that leverages students’ foundational understanding of chemistry to inform material selection decisions. Implemented over a 16-week semester with 88 students across 30 academically balanced teams, the activity emphasized teamwork, inquiry, and applied problem-solving. Quantitative results demonstrated a 73% improvement in conceptual understanding, as measured by pre- and post- intervention assessments. Qualitative analysis revealed enhanced articulation, critical thinking, and interdisciplinary application, particularly in connecting principles of chemical bonding and degradation to mechanical performance. Faculty observations and student feedback confirmed increased engagement, collaboration, and research curiosity. Aligned with the National Education Policy (NEP) 2020 and global engineering education trends, the model demonstrates strong potential for scalability across departments and institutions. It provides a practical framework for early research engagement, preparing students for complex, real-world challenges. The initiative affirms that embedding structured research into the core curriculum not only enhances academic outcomes but also transforms students into confident, inquiry-driven engineers.